TINGKAT KEPUASAN ORANG TUA TERHADAP PELAYANAN SMK PGRI 1 TANGERANG - Kurnaedi, Didi; Gumiwa, Aep (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2018)
Schools as lay educational institutions should provide a quality education especially for students, so that the students are satisfied with the ritual and show their attitude of loyalty to the school. This research is run in SMK PGRI 1 Tangerang to know the influence of service quality with satisfaction of student and their influence to loyalty mother to father of school. The sample of this study is 543 students of SMK PGRI 1 Tangerang class I, II and III as many as 1147 residents. This study uses a Likert Scale method used to measure the attitudes, opinions and perceptions of a person or group of people about social phenomena. Likert scale is used to measure public attitudes and perceptions about the satisfaction of the mother father with the reverence. The decision indicates that; (1) The quality of the service in SMK PGRI 1 Tangerang has a positive and significant impression for the mother of the students of SMK PGRI 1 Tangerang. (2) The satisfaction of the mother or student has a positive and significant impression on loyalty.